Межкультурные маркетинговые коммуникации предприятий в условиях макроэкономической интеграции - Карвицкая, Г. В.; Назаренко, Елена Васильевна; Егорова, О. Ю. (НТУ "ХПИ", 2014)
В статье утверждается, что стремление к повышению конкурентоспособности бизнеса в странах бывшего Советского Союза сопровождается адаптацией маркетинговых технологий к их национальной специфике. В условиях макроэкономической интеграции необходим регулярный мониторинг результатов рыночной деятельности предприятий во внутренней и внешней среде и оценка складывающегося имиджа.

In article it is claimed that the aspiration to increase of competitiveness of business in the countries of the former Soviet Union is accompanied by adaptation of marketing technologies to their national specifics. In the conditions of macroeconomic integration regular monitoring of results of market activity of the enterprises in internal both environment and an assessment of image which develops is necessary.
Cross-cultural marketing of communication of the company in conditions macroeconomic integration
Keywords: инновационные процессы; конкурентоспособность бизнеса; маркетинговые технологии; неформальные коммуникации; неудовлетворенность клиентов; экономическая интеграция; marketing communications; macroeconomic integration; informal communication; customer dissatisfaction